Molecular method confirms canine leishmania infection detected by serological methods in non-endemic area of Brazil - Riboldi, Emeline; Carvalho, Flavio; Romão, Pedro Roosevelt Torres; Barcellos, Regina Bones; Bello, Graziele Lima; Ramos, Raquel Rocha; de Oliveira, Rosemari Terezinha; Araújo Júnior, João Pessoa [UNESP]; Rossetti, Maria Lucia; Dallegrave, Eliane (Korean Society for Parasitology, 2018)
In Brazil, visceral leishmaniasis (VL) is expanding and becoming urbanized, especially in non-endemic areas such as the State of Rio Grande do Sul. Considering that infected dogs are the main reservoir for zoonotic VL, this study evaluated the prevalence of canine visceral leishmaniasis (CVL) in the metropolitan area of Porto Alegre, a new area of expansion of VL in Brazil. Serum and plasma from 405 asymptomatic dogs from the municipalities of Canoas (n= 107), São Leopoldo (n= 216), and Novo Hamburgo (n=82) were tested for CVL using immunochromatographic (DPP®) and ELISA EIE® assays (2 assays officially adopted by the Brazilian government for the diagnosis of CVL) and real-time PCR to confirm the results. There was no agreement among serological and real-time PCR results, indicating that the Leishmania infection in asymptomatic animals with low parasite load, confirmed by negative parasitological tests (smears and parasite culture), need to be evaluated by molecular methods. The prevalence of LVC in the metropolitan region of Porto Alegre, confirmed by real-time PCR was 4% (5.6% in Canoas and 4.6% in São Leopoldo). The use of molecular method is essential for accurate diagnosis of CVL, especially in asymptomatic dogs in non-endemic areas.
Keywords: Dog; Immunoassay; Leishmania sp.; Prevalence; Real-time PCR